Defining the Role of the Lower Limbs in Compensating for Sagittal Malalignment. Issue 22 (15th November 2017) - Lafage, Renaud; Liabaud, Barthelemy; Diebo, Bassel G.; Oren, Jonathan H.; Vira, Shaleen; Pesenti, Sébastien; Protopsaltis, Themistocles S.; Errico, Thomas J.; Schwab, Frank J.; Lafage, Virginie
Abstract : Study Design: Retrospective review. Objective: To investigate the role of lower limbs compensation with progressive sagittal malalignment. Summary of Background Data: Although lower limb compensatory mechanisms are established response to progressive sagittal malalignment, their specific role and potential impact on surgical planning has not been evaluated. Methods: Single center retrospective review of full body x-rays was performed in patients of age >20 years. Parameters were measured with dedicated software. Population was stratified by 50 mm intervals of sagittal vertical axis (SVA) and one-way ANOVA was performed to compare P.shift (P.shift = anteroposterior translation of the pelvis vs. the feet) across SVA groups. Anteroposterior offset of each vertebra in relation to a vertical line extended from the distal tibial metaphysis (TM) was investigated. Linear regression was performed to predict pelvic tilt (PT) using Knee angle (KA) and P.shift, whereas controlling for pelvic incidence minus lumbar lordosis mismatch (PI-LL) and SVA. Results: A total of 2124 patient visits were included (PI = 55.1 ± 14.1°, PT=21.0 ± 11°, PI-LL=6.3 ± 17.3°, SVA = 29 ± 51 mm). With progressively increased SVA, P.shift decreased from 30 to −100 mm (all P  < 0.005). Analysis of vertebral offset from the distal tibial metaphysis revealed that T9 was aligned with the TM line across all SVA groups. Prediction of PT based on PI-LL and SVA yielded R 2 =0.76 ( P  < 0.001). Subsequent addition of KA and P.shift as independent parameters using hierarchical multiple regression led to significant improvement in R 2, demonstrating the independent role of lower limbs parameters in PT prediction. KA and P.shift had a positive standardized coefficient (all P  < 0.05). Conclusion: Lower limb compensatory mechanisms increase with progressive sagittal malalignment. Anteroposterior translation of pelvis allows the T9 vertebra to remain in line with the ankle ("conus of economy"). Lower limb compensatory mechanisms are positive predictors of PT and thus do not require additional consideration in surgical realignment planning. Level of Evidence: 3